Practicality of Physics Learning Tools using Blended Learning Model with Video Assistance on Momentum and Impulse Materials to Improve Problem Solving Ability of Students - Susilawati Susilawati; Aris Doyan; Izlayani Putri; Muhammad Taufik (Pascasarjana, Mataram University, 2022)
This study aims to determine the practicality of physics learning tools using blended learning model with video assistance on momentum and impulse materials to improve problem solving ability of students. This research is development research, where researchers have developed learning tools with valid categories to further see the practicality of the devices developed after testing. The research design used is a 4D model consisting of define, design, develop and disseminate. The tools developed consist of a syllabus, lesson plans, student worksheets, teaching materials, learning videos, and problem-solving ability assessment instruments. The research instrument used was a student response questionnaire and an observation sheet on the implementation of learning. The results of the analysis show that the device meets the very practical criteria seen based on the positive response of students to learning reaching 97.48% in the very practical category, and the learning implementation observation sheet reaches an average of 93.77% in the very practical category. This shows that physics learning tools using a blended learning model with video assistance on momentum and impulse materials are very practical to improve problem-solving ability of students